2016
DOI: 10.1111/jpi.12320
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin mediates the stabilization of DELLA proteins to repress the floral transition in Arabidopsis

Abstract: Precise floral transition from vegetative growth phase to reproductive growth phase is very important in plant life cycle. In flowering genetic pathways, DELLA proteins are master transcriptional regulators of gibberelic acid (GA) pathway, and FLOWERING LOCUS C (FLC) is a core repressor of vernalization pathway as well as downstream of DELLAs. As a crucial messenger in plants, the possible involvement of melatonin (N-acetyl-5-methoxytryptamine) in flowering and underlying molecular mechanism are unknown in Ara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
55
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 73 publications
(58 citation statements)
references
References 58 publications
(121 reference statements)
3
55
0
Order By: Relevance
“…Although several physiological roles of melatonin in plants have been characterized [5,6,7,8,9,10,11,12,13,14,15,16,17,18,19,20,21,22], regulation of plant Fe deficiency responses and Fe homeostasis by melatonin have not been reported. The present study provided evidence that exogenous melatonin conferred improved plant adaptation to Fe deficiency by promoting Fe remobilization in Arabidopsis plants.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although several physiological roles of melatonin in plants have been characterized [5,6,7,8,9,10,11,12,13,14,15,16,17,18,19,20,21,22], regulation of plant Fe deficiency responses and Fe homeostasis by melatonin have not been reported. The present study provided evidence that exogenous melatonin conferred improved plant adaptation to Fe deficiency by promoting Fe remobilization in Arabidopsis plants.…”
Section: Discussionmentioning
confidence: 99%
“…In animals, melatonin is involved in regulating diverse physiological processes, such as biorhythms, seasonal reproduction, antioxidant functions, and immune stimulation [2,3,4]. Recently, much attention has also been attracted to study the functions of melatonin in plants; it acts as a crucial messenger molecule to regulate lateral root formation [5], flowering [6], fruit ripening [7], and leaf senescence [8]. Apart from its roles in plant growth and development, melatonin can improve the tolerance of plants to adverse environments [9,10,11,12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have shown that melatonin is widely involved in regulating both the biotic and abiotic stress tolerance, biological rhythms, plant growth and development (seed germination, root architecture, shoot development, plant flowering, fruit ripening, and yield; Kang et al, 2010; Okazaki et al, 2010; Wang et al, 2012; Byeon et al, 2013, 2014b; Yin et al, 2013; Zhang et al, 2013, 2014; Zhao et al, 2013; Byeon and Back, 2014a; Shi and Chan, 2014; Weeda et al, 2014; Shi et al, 2015a,b,c,d,e, 2016). …”
Section: Introductionmentioning
confidence: 99%
“…Melatonin, a growth regulator identified in higher plants in 1995, has been reported successively on regulating various biological processes, including root formation , flowering and fruit ripening (Shi et al, 2016), and leaf senescence (Wang et al, 2012 a). In particular, melatonin can trigger the plant defense responses against abiotic stress, playing an important role in improving the tolerance of plants to adverse environment (Li et al, 2012;Turk et al, 2014;Meng et al, 2015;Bałabusta et al, 2016).…”
Section: Introductionmentioning
confidence: 99%